The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.juro.2013.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Alvimopan, a Peripherally Acting μ-Opioid Receptor Antagonist, is Associated with Reduced Costs after Radical Cystectomy: Economic Analysis of a Phase 4 Randomized, Controlled Trial

Abstract: In patients treated with radical cystectomy alvimopan decreased hospitalization cost by reducing the health care services associated with postoperative ileus and decreasing the hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…Median time to first BM with alvimopan was 5 days, similar to the 4.9 days reported by the RCT, and it was 6 days without alvimopan, comparable to the 6.1 days in the placebo arm. Postoperative LOS was similar to that reported in the RCT (6 vs. 7 days in alvimopan group, 8 vs. 8 days in non-alvimopan group), and use of TPN was comparable based on the reported phase IV data (3.7 vs. 10% in alvimopan group, 22.4 vs. 25% in non-alvimopan group) [7]. Additionally, our patient population was similar to that of the RCT, being predominately white males who were current or former smokers, and the distribution of surgical approaches for RC (i.e.…”
Section: Discussionsupporting
confidence: 81%
“…Median time to first BM with alvimopan was 5 days, similar to the 4.9 days reported by the RCT, and it was 6 days without alvimopan, comparable to the 6.1 days in the placebo arm. Postoperative LOS was similar to that reported in the RCT (6 vs. 7 days in alvimopan group, 8 vs. 8 days in non-alvimopan group), and use of TPN was comparable based on the reported phase IV data (3.7 vs. 10% in alvimopan group, 22.4 vs. 25% in non-alvimopan group) [7]. Additionally, our patient population was similar to that of the RCT, being predominately white males who were current or former smokers, and the distribution of surgical approaches for RC (i.e.…”
Section: Discussionsupporting
confidence: 81%
“…Numerous attempts have been made to reduce the incidence of gastrointestinal complications after RC, including gum chewing, medications targeting the peripheral m-opioid receptor, and fast track regimens. [25][26][27] However, these efforts are a series of conservative measures and should serve as adjunctive therapies, because the surgery itself has a much greater affect on the occurrence and development of POI. Kulkarni et al 12 first described extraperitoneal radical cystectomy using a retrograde technique in 1999.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Bell and colleagues 10 performed an economic evaluation of the 4 pooled alvimopan North American bowel resection trials and demonstrated a costs savings of $977 per patient when implementing alvimopan. Touchette and colleagues 12 based their economic analysis on a published meta-analysis of 3 US phase 3 bowel resection clinical trials and used a sensitivity analysis based on the international phase 3 clinical trial data.…”
Section: Discussionmentioning
confidence: 99%
“…However, such a potential offset in nonalvimopan pharmacy costs was not observed in the radical cystectomy trial reported by Kauf and colleagues. 11 In addition, the duration of alvimopan dosing in the model was estimated based on dosing observed in the trials (ie, given up to discharge). However, realworld studies report mean durations of alvimopan therapy that reflect fewer doses than would be incurred if given up until discharge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation